2020
DOI: 10.1038/s41598-020-63861-4
|View full text |Cite
|
Sign up to set email alerts
|

Author Correction: Inhibition of Porphyromonas gulae and periodontal disease in dogs by a combination of clindamycin and interferon alpha

Abstract: In addition, a canine IFN-α formulation (InterBerryα ® ; Hokusan Co. Ltd., Higashihiroshima, Japan) has been commercially available as a pharmaceutical agent for periodontal treatment in animals since 2014. " should read: "In addition, a canine IFN-α formulation (InterBerryα ® ; Hokusan Co. Ltd., Kitahiroshima, Japan) has been commercially available as a pharmaceutical agent for periodontal treatment in animals since 2014. "

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…It has been reported that P. gulae is susceptible to clindamycin, which has been approved for the treatment of periodontal disease in dogs ( 14 , 15 ). Recently, our group showed that combination therapy using clindamycin and IFN-α treatment can improve periodontal condition and reduce P. gulae in dogs ( 13 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that P. gulae is susceptible to clindamycin, which has been approved for the treatment of periodontal disease in dogs ( 14 , 15 ). Recently, our group showed that combination therapy using clindamycin and IFN-α treatment can improve periodontal condition and reduce P. gulae in dogs ( 13 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, type C induces even higher systemic inflammation than the other genotypes ( 11 , 12 ). Indeed, type C is considered to be the most virulent of the genotypes, as it is predominant in the oral cavities of dogs with severe periodontitis ( 12 , 13 ). However, previous studies only demonstrated fimA Type C may be found more frequently in severe disease samples and have the ability to cause more inflammation than other types in a mouse model, this does not prove causation of periodontitis in dogs.…”
Section: Introductionmentioning
confidence: 99%